2023
DOI: 10.1021/jacs.3c09081
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurative Borylation of Small Molecules, Peptides, and Proteins

Ruiheng Jing,
Wyatt C. Powell,
Kyle J. Fisch
et al.

Abstract: We introduce a direct conversion of alkyl thiols into boronic acids, facilitated by a water-soluble phosphine, 1,3,5triaza-7-phosphaadamantane (PTA), in conjunction with tetrahydroxydiboron (B 2 (OH) 4 ), acting as both a radical initiator and a boron source. This desulfurative borylation reaction has been successfully applied to various substrates, including cysteine residues in oligopeptides and small proteins, primary alkyl thiols found in pharmaceutical compounds, disulfides, and selenocysteine. Optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Several methods for the desulfurisation of Cys residues have been reported in the literature, these include; photo-induced desulfurisation 69 using a ruthenium PC, 60 photo-desulfurisation in flow, 61 accelerated desulfurisation using tetraethylborate (NaBEt 4 ), 63 desulfurative borylation, 64 and the exploitation of phosphite 66 and phosphine-dependent pathways. 65 We attempted to adapt and explore two appropriate examples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for the desulfurisation of Cys residues have been reported in the literature, these include; photo-induced desulfurisation 69 using a ruthenium PC, 60 photo-desulfurisation in flow, 61 accelerated desulfurisation using tetraethylborate (NaBEt 4 ), 63 desulfurative borylation, 64 and the exploitation of phosphite 66 and phosphine-dependent pathways. 65 We attempted to adapt and explore two appropriate examples.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 Desulfurisation of Cys (and alternative non-proteinogenic thiol-containing amino acids 56–58 ) can be applied post-peptide ligation as an elegant method to access a broad range of ligation junctions and facilitate chemical protein synthesis. 56,59–67 A widely used free-radical-mediated Cys desulfurative protocol, 59 developed by Danishefsky and co-workers, proceeds via a thiophosphoranyl radical species generated using a radical initiator (VA-044) to form a thiyl radical from the thiol sidechain of Cys in the presence of the water-soluble phosphine, tris(2-carboxyethyl)phosphine hydrochloride (TCEP). β-Scission of the thiophosphoranyl radical 62 produces a peptide ‘alanyl’ radical which, in the presence of a suitable thiol additive ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported a direct borylation of cysteine residues in peptides and proteins forming boronoalanine . During these studies, we observed the formation of small amounts of alanine byproducts, which could be suppressed by a judicious selection of a phosphine additive and by adjusting the concentrations of the reagents.…”
mentioning
confidence: 92%
“…Furthermore, experiments with various diboron sources yielded complex mixtures (B 2 pin 2 and B 2 neo 2 , entries 7 and 8, respectively) or reduced the yield of 2a (B 2 cat 2 and B 2 (NMe 2 ) 4 , entries 9 and 10, respectively). Notably, a high concentration of B 2 (OH) 4 without any phosphine could also produce desulfurized product 2a as well as borylated product 2c (entry 11), which implied the possible desulfurize mechanism with only B 2 (OH) 4 . We also ran the reaction in the absence of B 2 (OH) 4 but obtained only trace amounts (<1%) of 2a .…”
mentioning
confidence: 99%
“…To overcome this problem, selective photochemical strategies have been developed to generate boronoalanine from cysteine residues in unprotected peptides and proteins (Figure 1C ). [ 12 ]…”
Section: Introductionmentioning
confidence: 99%